SISTEM INFORMASI REKAP BUKU ONLINE MENGGUNAKAN METODE WATERFALL - Andri Suryadi (STMIK Royal, 2020)
Abstract: The development of Information Technology in the field of education, a survey on the Use and Utilization of Information and Communication Technology was carried out on 4,014 schools in 34 provinces. Based on the level of education, elementary and equivalent as much as 64.55 percent, junior high school and equivalent as much as 19.22 percent and high school and equivalent as much as 16.23 percent. While the use of applications in the field of education is still felt to be lacking especially in rural schools so that there is a gap between urban schools and rural schools. This condition occurs in SMP PGRI Malangbong where the use of applications is still lacking. One example is in the recording of books in schools that are still manual which complicates operations in the school. The solution offered is to create an online book recapitulation system which is expected to be very useful for school operations. The online book recapitulation system was built using the waterfall method starting from the analysis, design, implementation, testing to maintenance stages. Keywords: Book Information system; Books; Schools Abstrak: Perkembangan Teknologi Informasi di bidang pendidikan, survei Penggunaan dan Pemanfaatan Teknologi Informasi dan Komunikasi dilakukan terhadap 4.014 sekolah yang tersebar di 34 provinsi. Berdasarkan jenjang pendidikan, SD dan sederajat sebanyak 64,55 persen, SMP dan sederajat sebanyak 19,22 persen dan SMA dan sederajat sebanyak 16,23 persen. Sedangkan penggunaan aplikasi dibidang pendidikan masih dirasa kurang terutama di sekolah-sekolah pedesaan sehingga terjadinya kesenjangan antara sekolah diperkotaan dan sekolah pedesaan. Kondisi tersebut terjadi pada SMP PGRI Malangbong dimana penggunaan aplikasi masih sangat kurang. Salah satu contohnya adalah dalam perekapan buku di sekolah yang masih bersifat manual yang menyulitkan operasional di sekolah tersebut. Solusi yang ditawarkan adalah dengan membuat sistem rekap buku online yang diharapkan sangat berguna bagi operasional sekolah. Sistem rekap buku online ini dibangun menggunakan metode waterfall mulai dari tahap analisis, desain, implementasi, pengujian sampai dengan pemeliharaan. Kata Kunci : Buku Sekolah; Sistem Informasi Rekap Buku